GENETIC DIVERSITY OF BROILER CHICKEN BRANDS RAISED IN ARID AND SEMI-ARID ZONES OF NORTHERN NIGERIA USING MITOCHONDRIAL DNA - Abdullahi, A. Y.; Nasir, M.; Khalee, A. G.; Ashiru, R. M.; Zango, H. M.; Madaki, S.; Ha, H. C.; Ismail, N.; Ahmad-Syazni, K. (FUDMA JOURNAL OF SCIENCES, 2021)
A sector of broiler production is growing very fast to meet the high demand of meat in Nigeria. However, high mortality rates among the broilers especially during the hot dry season in arid and semi-arid zones is worrisome. There is a need for molecular genetics study that could aid in management, conservation and sustainable exploitation of this species. To evaluate the genetic diversity of broilers raised in these regions, a total of forty-six broilers were randomly sampled from eight different brands (Agrited, Amo, Chi, Fol-hope, Obasanjo, Olam, Yammfy and Zatech) for mitochondrial DNA analysis. Four haplotypes were detected among all the samples used that belong to the four strains. The sequences of mitochondrial regions revealed high haplotype diversity (0.78600) and low nucleotide diversity (0.00286). Lower genetic diversity observed may increase the chances of rapid disease infection and distribution during any disease outbreak. Introduction of new strains of broilers with high genetic diversity is highly recommended. Future study should be conducted on the performance of these strains during the extremely hot temperature period in arid and semi-arid zones of Nigeria. This is to provide reliable information for the sake of local broiler farmer’s benefit who invests largely on this sector. The study will also help the geneticists from these brands to develop a strain that could survive and perform excellently under severe climatic conditions of the rural areas of arid and semi-arid zones of Nigeria